Antecedents and consequences of brand experience in virtual sports brand communities: A value co-creation perspective - Zhuo, Jin-Yuan; Su, Rong-Hai; Yang, Hsi-Hsun; Hsu, Mao-Chou (Frontiers in Psychology, 2022)
The influence mechanism for brand experience in virtual sports brand communities is the subject of many studies, but these studies do not feature a holistic consideration of antecedents and consequences, and the moderating role of brand attachment is unclear. Drawing on the value co-creation theory, this study determines the impact of brand experience and its mechanism using the data from 508 virtual sports brand communities. The empirical test results show that value co-creation (i.e., corporate-initiated value co-creation and customer-initiated value co-creation) has a positive effect on the brand experience and that the brand experience has a positive effect on the purchase intention. Brand attachment does not have a moderating role between brand experience and purchase intention so as the degree of brand attachment increases, the brand experience does not increase the purchase intention through a brand attachment. This study determines the antecedents and consequences of brand experience in virtual sports brand communities from a value co-creation perspective, to determine the impact and mechanisms of virtual sports brand communities to guide the marketing practices of virtual sports brand communities.